2020
DOI: 10.2116/analsci.20scn02
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Malachite Green-Induced Toxicity to Human Liver Cells Utilizing Host-Guest Chemistry of Cucurbit[7]uril

Abstract: We investigated a host-guest complex between cucurbit[7]uril and malachite green, and its effect on the toxicity to human liver cells. The host-guest complexation was evaluated by a UV/vis titration and electrospray-ionization mass spectrometry. Interestingly, the host-guest complex resulted in remarkable suppression of the toxicity of malachite green in its practical concentration range (ca. ~6 µM). This study is one step forward to the active control of the biological effects of potent toxicants utilizing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…There are numerous variables that influence the toxicity of certain toxicants, such as the temperature, pH, and hardness of the test water, making it difficult to analyse the effects on diverse species of fish [5][6][7][8][9]. The question of whether MG is teratogenic to fish has been investigated in great detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous variables that influence the toxicity of certain toxicants, such as the temperature, pH, and hardness of the test water, making it difficult to analyse the effects on diverse species of fish [5][6][7][8][9]. The question of whether MG is teratogenic to fish has been investigated in great detail.…”
Section: Introductionmentioning
confidence: 99%
“…Many other research, both clinical and experimental, have been conducted on MG over the years. Its toxicity to diverse organisms, aquatic and terrestrial has been reported [5,[7][8][9][10][11][12][13][14][15]] and its removal is thus warranted. Biodegradation of MG has been touted as an important aspect of MG bioremediation.…”
Section: Introductionmentioning
confidence: 99%